Resposta linfóide em biópsias gástricas de crianças do Hospital Universitário Antonio Pedro: associação com Helicobacter pylori e com vírus Epstein-Barr - Carvalho, Angela Cristina Gouvêa (2006)
The infection by Helicobacter pylori (H.pylori) can be related to the occurrence of carcinomas and MALT lymphomas, while the latent infection by Epstein-Barr virus (EBV) is associated both to gastric epithelial malignant neoplasias as to lymphomatous gastric epithelial neoplasias. The purpose of this study was to perform a systematic and global histopathological analysis of gastric biopsies from children submitted to upper digestive endoscopy, with recurrent abdominal pain, in Antonio Pedro University Hospital/UFF and to study the association between lymphoid proliferation and H.pylori and EBV. The gastric biopsies (n=142) from children up to 12 years old (n=129; 52% male; age 8±3 years) from January 2002 to December 2004 were reviewed and the slides were stained with Giemsa and Whartin-Starry for identification of H.pylori and immunostains for EBV (anti-LMP1) and T-lymphocytes CD8+ were used. Under light microscopy, 63% presented chronic gastritis and 30% infection by H.pylori. Forty-eight percent of children with chronic gastritis had lymphoid proliferation, but 15 among these were negative for H.pylori. None of the children was positive for EBV and 83% of them presented up to five T CD8+ lymphocytes per 100 superficial epithelial cells. H.pylori positive children were older than the negative ones (9.1±2.8 vs. 7.1±3.3 years; P<0,001) and the presence of lymphoid response was more frequently found in children with H.pylori (80% vs. 15%; P <0,001). In conclusion, EBV is not related to lymphoid response in children gastric biopsies. However, this lymphoid proliferation is associated with H.pylori infection in 48% of children with chronic gastritis. Five out of 15 children with lymphoid proliferation but negative for H.pylori, had been previously treated for this bacteria, suggesting that this response could be post-treatment sequelae. The remaining 10 biopsies could represent post-treatment sequelae from other systemic infections.